Characterization of Oxygenated Propenylbenzene Derivatives Binding to MAO-A Using Isothermal Titration Calorimetry and Molecular Modeling - Joanna Grzelczyk; Horacio Pérez-Sánchez; Miguel Carmena-Bargueño; Ilona Gałązka-Czarnecka; Grażyna Budryn; Dawid Hernik; Elisabetta Brenna; Filip Boratyński (Applied Sciences)
Monoamine oxidase A (MAO-A) is the main enzyme that deaminates serotonin. Correct serotonin concentration regulates appetite, improves well-being, reduces symptoms of depression, but also improves memory and heart function. In this study, the use of new compounds chemo-enzymatically synthesized from propenylbenzene derivatives as MAO-A inhibitors was proposed. Isothermal titration calorimetry analysis and molecular modeling were used to determine the inhibitory effect of MAO-A. The main compounds such as propenylbenzenes were observed to have no inhibitory effect. However, in the case of diols and hydroxy ketones, the compounds showed MAO-A inhibitory effects. In particular, 1-(4-hydroxy-3-methoxyphenyl)propane-1,2-diol, both in isothermal titration calorimetry (ITC) and molecular modeling, showed high affinity for the MAO-A enzyme, thus protecting serotonin from deamination. The results suggest that propenylbenzene derivatives, such as diols and hydroxy ketones, bind to MAO-A at the active site. This suggests their potential to be used as drugs or food supplements to prevent depression. These studies may constitute a new tool for further in vivo and in vitro studies.